Hypothyroidism and its influence on maternal and perinatal outcomes: insights from a hospital-based retrospective study - Ahmad, Bushra; Chaudhary, Naima; Srivastava, Shipra; Sharma, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypothyroidism during pregnancy is a prevalent endocrine disorder that significantly impacts maternal and perinatal health in the form of infertility, early pregnancy loss, PIH, anaemia, IUGR, PROM, preterm labour, neonatal mortality and morbidity. This retrospective hospital-based study aimed to evaluate the maternal and fetal outcomes associated with hypothyroidism in pregnant women. Methods: Medical records of pregnant women diagnosed with hypothyroidism were reviewed to assess clinical characteristics, treatment status, and pregnancy outcomes. Maternal complications such as anaemia, preeclampsia, PPH, hypertension, miscarriage were recorded alongside perinatal outcomes including preterm birth, low birth weight, and intrauterine growth restriction. A total of 550 antenatal women with singleton pregnancies and without any pr-existing medical disorder were screened. All patients were monitored up to the point of delivery, allowing for comparison of outcomes across the three groups. Results: Among the study cohort of 550 antenatal women, 70 were found to have hypothyroidism with an estimated prevalence of 12.72, largely comprising subclinical cases. A higher incidence of hypothyroidism was seen among multigravida patients. Lower segment cesarean section (LSCS) was the most common mode of delivery in the women with hypothyroidism. In addition, hypothyroid mothers experienced higher incidences of adverse outcomes such as preeclampsia, miscarriage, preterm labor, low birth weight infants, IUGR, foetal distress and need for NICU admission as compared to euthyroid mothers. Early identification and treatment with levothyroxine were associated with improved maternal and fetal outcomes. Conclusions: Hypothyroidism in pregnancy is associated with significant risks for both mother and child. Routine screening and timely treatment are critical measures to mitigate these risks and improve pregnancy outcomes. The findings highlight the necessity of universal thyroid function screening protocols in antenatal care to ensure optimal maternal and perinatal health.